A new species of Buprestis subgenus Akiyamaia from South-Eastern Tibet, China (Coleoptera: Buprestidae: Buprestini) - Huang, Hao; Pan, Zhao-Hui (Zootaxa, 2015)
Buprestis (Akiyamaia) intercostata sp. n. is described from Chayu, south-eastern Tibet. It is characterized by the presence of three additional longitudinal carinae inserted between the elevated suture and the three normal costae commonly found on each elytron of the previously known species of Akiyamaia.